Gallotannin is a DNA damaging compound that induces senescence independently of p53 and p21 in human colon cancer cells. Issue 10 (6th May 2014) - Al‐Halabi, Racha; Abou Merhi, Raghida; Chakilam, Saritha; El‐Baba, Chirine; Hamade, Eva; Di Fazio, Pietro; Ocker, Matthias; Schneider‐Stock, Regine; Gali‐Muhtasib, Hala
Abstract : The plant secondary metabolite gallotannin (GT) is the simplest hydrolyzable tannin shown to have anti‐carcinogenic properties in several cell lines and to inhibit tumor development in different animal models. Here, we determined if GT induces senescence and DNA damage and investigated the involvement of p53 and p21 in this response. Using HCT116 human colon cancer cells wildtype for p53 +/+ /p21 +/+ and null for p53 +/+ /p21 −/− or p53 −/− /p21 +/+, we found that GT induces senescence independently of p21 and p53. GT was found to increase the production of reactive oxygen species (ROS) by altering the redox balance in the cell, mainly by reducing the levels of glutathione and superoxide dismutase (SOD). Using the key antioxidants N ‐acetyl cysteine, dithiothreitol, SOD, and catalase, we showed that ROS were partially involved in the senescence response. Furthermore, GT‐induced cell cycle arrest in S‐phase in all HCT116 cell lines. At later time points, we noticed that p53 and p21 null cells escaped complete arrest and re‐entered cell cycle provoking higher rates of multinucleation. The senescence induction by GT was irreversible and was accompanied by significant DNA damage as evidenced by p‐H2AX staining. Our findings indicate that GT is an interesting anti colon cancer agent which warrants further study. © 2014 Wiley Periodicals, Inc.